Information security : the complete reference - Rhodes-Ousley, Mark (McGraw-Hill Education, 2013)
This title offers vendor-neutral details on all aspects of information protection, with an eye toward the evolving threat landscape. Thoroughly revised and expanded to cover all aspects of modern information security--from concepts to details--this edition provides a one-stop reference equally applicable to the beginner and the seasoned professional -- from publisher description